Irrigated agricultural production dynamics in response to rainfall variability and water policy reforms in the southern Murray-Darling Basin of Australia - Ketema Zeleke; David J. Luckett (Agricultural Water Management)
The Murray-Darling Basin water market dataset was used to assess the change in cropping mix, the relationship between water demand and supply factors, and the trend in irrigation area and production of major irrigation crops in the past two decades. The introduction of innovative water policies such as interregional water trading and intertemporal water transfers via the carryover of unused water allocations (in public dams) from one year to the next were found to be key interventions to manage the Basin’s water resources efficiently and sustainably. Cotton is replacing rice as an alternative annual broadacre crop in the Murrumbidgee catchment. As a result, rice is grown as an opportunistic crop only in more ideal years in terms of rainfall and/or availability of irrigation water. In the Victorian Murray region below the Barmah Choke, almond plantation water use has grown by almost 185 % in the past two decades mainly by replacing pasture, and by using water available on the market from the upstream catchments in Victoria and New South Wales. Carryover water stabilises water price and, in drought years, increases agricultural production as water price is highly correlated with water availability (dam levels). There is a significant positive correlation between general (i.e. “low”) security water allocation and rice production, and the gross value of irrigated agricultural production (GVIAP) of rice. There is also a significant positive correlation between carryover and agricultural production and GVIAP. Water markets and carryover were found to be important water policy measures to manage temporal and spatial irrigation water availability and variability.